Styrene solve - Khairul Anuar, Hussin; Mazni, Zakaria; Nur Izzati, Mohamad Sobri; Nurliyana, Ariffin; Wan Nurhazirah, Kamaruzaman (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.